Improving the surface chemistry of upconverting nanoparticles for use in immunoassays based on single molecule enumeration - Raiko, Kirsti (My University, 2020)
Upconverting nanoparticles (UCNPs) are luminescent nanosized crystals, which emit higher energy light than the excitation light. This anti-Stokes fluorescence enables autofluorescence-free and highly sensitive detection in complex biological matrices, which makes them excellent alternatives for reporters in diagnostic applications. For these purposes, monodispersity of bioconjugated UCNPs in biological fluids and low non-specific binding are crucial. Both of these properties are significantly influenced by surface chemistry. The aim of this study was to improve the surface chemistry of UCNPs to produce hydrophilic particles, which are stably monodispersed in biological matrices and exhibit low non-specific binding in immunoassays. Their applicability in homogeneous and heterogeneous immunoassay formats based on single molecule enumeration was studied. Synthesized oleic acid-coated UCNPs were rendered hydrophilic via acid treatment or by ligand exchange via nitrosyl tetrafluoroborate (NOBF4) prior to coating with poly(acrylic acid) (PAA), either in water or DMF. Monodispersity was studied via transmission electron microscopy, agarose gel electrophoresis and filtration tests, and the non-specific binding via immunoassays using non-bioconjugated UNCPs. A digital heterogeneous immunoassay in plasma and an upconversion cross-correlation spectroscopy-based immunoassay in buffer and in plasma were conducted. The ligand exchange with NOBF4 prior to PAA coating in DMF yielded monodisperse particles with minor to no aggregation observed. The non-specific binding was two times lower with the developed coating compared to acid treated particles with PAA coating in water. These advances were shown to facilitate the use of the UNCPs in single molecule enumeration -based immunoassays.
Keywords: poly(acrylic acid), monodispersity, non-specific binding